Youth Employment in Nepal - Raju, Dhushyanth; Rajbhandary, Jasmine (Washington, DC: World Bank, 2018)
Promoting the smooth labor market integration and early labor market success of workers has increasingly become an important economic and social development aim globally. The Nepal government sees addressing the social and economic challenges of youth, and leveraging their social and economic prospects, as critical for the country’s economic growth and development. There has been limited systematic, policy-oriented empirical research conducted on labor and livelihoods in Nepal. Dedicated examinations of the labor conditions, behaviors, and outcomes of youth are rarer still. Responding to the knowledge needs expressed by the Nepal government and other stakeholders in the country, this book aims to improve our understanding of the labor market conditions, behaviors, and outcomes of Nepalese youth. It examines these aspects in Nepal’s domestic labor market as well as in relation to labor migration to India and other countries, including temporary 'foreign employment' of Nepalese workers under bilateral labor agreements between destination countries and Nepal. In so doing, the report seeks to present insights and implications for research and public policy, with the goal of improving the labor market prospects of Nepalese youth. The collective findings in the report point to three directions for orienting public policy and program initiatives. First is raising rural labor productivity, urban labor demand, and urban worker–job matching efficiency. Second is supporting the labor market integration of rural youth migrating to urban parts of Nepal and of youth labor migrants returning from India and other countries. Third is improving the orientation and efficacy of labor skill training.